2014
DOI: 10.13101/ijece.7.56
|View full text |Cite
|
Sign up to set email alerts
|

Landslide-triggering Rainfall Thresholds after Major Earthquakes for Early Warning

Abstract: Early-warning systems for natural disasters are important tools for disaster risk reduction. In 2005, the Japanese government initiated a new nationwide early-warning system for landslide disasters. The system uses the RBFN method to set the criterion (Critical Line: CL) primarily based on rainfall data recorded as not triggering disasters. Moreover, after large earthquakes, the thresholds (CL) are scaled down by 20-50%, considering the seismic disturbances in the slopes. In this study, we examined the validit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…A field survey revealed that many fissures were formed and a large amount of sediments remained unstable on ridgelines and hill slopes (Osanai et al 2019). It is known that slope failures and debris flows, which can affect residents downstream, are more likely to occur during heavy rain after a major earthquake due to fissures and unstable landslide materials produced by the earthquake (Nomura et al 2014;Sidle et al 2018). A prolonged increase in sediment and driftwood discharge, which can cause flooding due to riverbed aggradation and bridge blockage, followed by water quality deterioration, can occur after devastation of an upper stream (Koi et al 2008;Uchida et al 2014;Marc et al 2015).…”
Section: Densely Distributed Shallow Landslidesmentioning
confidence: 99%
“…A field survey revealed that many fissures were formed and a large amount of sediments remained unstable on ridgelines and hill slopes (Osanai et al 2019). It is known that slope failures and debris flows, which can affect residents downstream, are more likely to occur during heavy rain after a major earthquake due to fissures and unstable landslide materials produced by the earthquake (Nomura et al 2014;Sidle et al 2018). A prolonged increase in sediment and driftwood discharge, which can cause flooding due to riverbed aggradation and bridge blockage, followed by water quality deterioration, can occur after devastation of an upper stream (Koi et al 2008;Uchida et al 2014;Marc et al 2015).…”
Section: Densely Distributed Shallow Landslidesmentioning
confidence: 99%
“…After large earthquakes (more than level 5+ on the Japanese scale), it is well-known that the thresholds (CL) of landslide occurrence should be scaled down [Nomura et al ., 2014]. So that, after the main shock with a seismic intensity of 7 (at 1 : 25, 16 th April, M 7.3) in Mashiki-town, and Nishihara-village, 70% of the original threshold was applied to 23 towns and villages in which the earthquake with intensity of more than minor 6 was observed while 80% of the original was applied to 8 towns and villages in which the earthquake with intensity over 5 was observed (Fig.…”
Section: Fig1 Locations Of the Main Sediment Disasters In Kumamoto Pmentioning
confidence: 99%